2013
DOI: 10.1186/1471-2407-13-86
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Albendazole and 2-Methoxyestradiol significantly improves the survival of HCT-116 tumor-bearing nude mice

Abstract: BackgroundAlbendazole (ABZ) is a microtubule-targeting anthelmintic with a remarkable activity against a variety of human cancer cells. In this study, we examined if the antitumor activity of ABZ could be enhanced by its combination with other microtubule-binding agents.MethodsThe interactions between ABZ and microtubule-binding agents, paclitaxel, vinblastine, colchicine, and 2-methoxyestradiol were characterized using median effect analysis method in HCT-116 colorectal cancer cells and DU145 prostate cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…The groups received intraperitoneal injections of 200 lL NaCl/P i , CDDP (10 mgÁkg À1 ), YM155 (3 mgÁkg À1 ) or TCN (2 mgÁkg À1 ) every 3 days, or 2ME2 (25 mgÁkg À1 ) daily, or various combinations as indicated. The doses for each reagent used in the study have previously been reported to be effective in mice [32,44,45]. Mice were killed on day 15.…”
Section: Cell Viability and Apoptosis Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The groups received intraperitoneal injections of 200 lL NaCl/P i , CDDP (10 mgÁkg À1 ), YM155 (3 mgÁkg À1 ) or TCN (2 mgÁkg À1 ) every 3 days, or 2ME2 (25 mgÁkg À1 ) daily, or various combinations as indicated. The doses for each reagent used in the study have previously been reported to be effective in mice [32,44,45]. Mice were killed on day 15.…”
Section: Cell Viability and Apoptosis Assaysmentioning
confidence: 99%
“…The doses for each reagent used in the study have previously been reported to be effective in mice [32,44,45]. Mice were killed on day 15.…”
mentioning
confidence: 99%
“…Research on ABZ antitumor activity has been carried out on ovarian cancer cell lines [23,24], and other studies were performed on HCT-116 (a colorectal cancer cell line) in which ABZ was formulated as hydroxypropyl-β-cyclodextrin (HP-β-CD) inclusion complexes [25,26]. Castro et al (2016) reported an interesting study on MCF7 breast cancer cells, showing that ABZ promotes oxidative DNA damage, which induces DNA fragmentation, apoptosis, and cell death [1].…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the treatment, the gavage tube was left in place for several seconds to avoid regurgitation and ensure the total calculated dose was administered. e tumor sizes were monitored every 2 days using a digital caliper, and the tumor volumes were calculated using the formula: L × S 2 × 0.5, where L and S represent the longest and shortest tumor diameters, respectively [31]. e mice were also weighed.…”
Section: Animal Experimentsmentioning
confidence: 99%